Synthesis, Properties, and In Vitro Hydrolytic Degradation of Poly(d,l-lactide-co-glycolide-co-ε-caprolactone) - Yixiu Liu; Xizhuang Bai; A. Liang (International Journal of Polymer Science)
Random copolymers of poly(d,l-lactide-co-glycolide-co-ε-caprolactone) (PLGC) were synthesized by the ring-opening polymerization of d,l-lactide (DLLA), glycolide (GA), and ε-caprolactone (CL). The effects of CL on the copolymers were evaluated to prepare suitable copolymers with controlled properties. Our results showed that the CL content significantly influenced the thermal and mechanical properties of the copolymers and that the CL content in compositions could be altered to control properties of random copolymers. The in vitro hydrolytic degradation of the resulting implants showed that the degradation rate of PLGC was lower than that of PLGA, which could markedly reduce acidic degradation products. Finally, we demonstrated that higher CL contents in compositions slowed degradation rates.